KANDUNGAN SERAT KASAR AMPAS SAGU HASIL FERMENTASI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DENGAN PENAMBAHAN UREA - Insun Sangadji; Ch W Patty; Jerry F Salamena (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
The aim of this experiment was to determine crude fiber content of sago by product fermented with White Root fungi and urea. The treatments were imposed in a Randomized Complete Design with three replications. The treatments were ration with: medium without White Root fungi and urea (R0), medium with White Root fungi (R1), medium with White Root fungi and 0,25% urea (R2), medium with White Root fungi and 0,50% urea (R3). Parameters measured were NDF, ADF, and lignin. The results showed that all components of crude fiber decreased during fermentation periods with White Root fungi (Pleurotus ostreatus) and urea. The average NDF content of fermented sago-by products were 57,27%, 51,25%, 52,37%, and 50,94% for R0, R1, R2, and R3, repectively. There was significant differences between R1, R2. R3 and R0 (P<0,05). The average ADF content of fermented sago-by products were 49,54%, 47,58%, 46,75, and 45,14% for R0, R1,R2, and R3 respectively. There was significant differences between R1, R2, R3 and R0 (P <0,05). Statistical analysis showed significant difference in ADF content between R3 and R0. The average lignin content of fermented sago-by products were 6,64%, 5,74%, 5,39%, and 5,41% for R0, R1, R2, and R3, respectively. There were no significant differences among the treatments. It be can concluded that sago-by product fermented with white root fungi and 0,50% urea decreased crude fiber components.